Phase portraits on the unit sphere of the stretch-twist-fold flow - Llibre, Jaume; Valls, Claudia (Nonlinear Analysis: Modelling and Control, 2023)
The so-called stretch-twist-fold flow consists in a Stokes flow depending on two parameters defined in a unit closed ball B that is associated with the motion of a fluid particle coming from the dynamo theory, and it models a mechanism for studying the magnetic field of the Earth and the Sun. Here for the first time, we classify all the local phase portraits of its equilibrium points, and we provide the global phase portraits on the 2-dimensional sphere of the boundary of the ball B.
Keywords: stretch-twist-fold flow; equilibrium points; local phase portraits; global phase portraits